Reclamation of Degraded Soil through Tree Plantation - Litter and Fertility Changes - Das, D. K.; Chaturvedi, O. P.; Mandal, M. P.; Kumar, R. (Indian Forester, 2007)
This paper evaluates the relative efficacy of plantations of different tree species in improvement of high pH soil. The 12 tree species studied in general were effective in bringing about improvement in the soil properties as reflected by the changes in pH, EC, organic carbon, available nitrogen, phosphorus and potassium. Higher available N, P2O5 and K2O as well as higher organic carbon percentage were noted under canopy of Albizia procera followed by Leucaena leucocephala. The pH and EC were lowest under Albizia procera and changes were observed from 8.7 to 7.7 and 0.76 to 0.40 dS m-1, respectively in the span of 12 years. Albizia procera produced maximum litter fall (13.95 t ha-1year-1) followed by Leucaena leucocephala (13.25 t ha-1year-1) plantation. The nutrients returned through litter fall followed the order N>K>P in all the tree species and was helpful in reclamation of high pH soils.